Cross‐ecosystem effects of a large terrestrial herbivore on stream ecosystem functioning. Issue 1 (24th September 2018) - MacSween, Jessica; Leroux, Shawn J.; Oakes, Ken D.
Abstract : Large terrestrial consumers have direct and indirect effects on forest ecosystem function, but few studies have investigated the impacts of terrestrial consumers on freshwater ecosystems. In the Cape Breton Highlands of Nova Scotia, browsing by hyper‐abundant moose following a spruce budworm outbreak has transformed boreal forest into grasslands. We conducted a field study to investigate the potential for cross‐ecosystem effects of hyper‐abundant moose following budworm outbreak on small boreal stream ecosystem structure and function. With our field study, we tested the prediction that watersheds with higher levels of moose‐mediated grasslands in their sub‐basin would have higher stream temperatures, total nitrogen, electrical conductivity, periphyton biomass and macroinvertebrate abundances. While our data supported several of our predictions pertaining to moose impacts on the abiotic variables (i.e. temperature range, total nitrogen, electrical conductivity) we found evidence of variable moose impacts on the benthic community. Specifically, we observed lower relative abundance of predatory invertebrates in streams with high moose impacts compared to streams with low moose impacts in their watersheds but no evidence of moose impacts on the relative abundance of shredders, filterers, gatherers, and grazers. This empirical study fills a key gap in our understanding of spatial ecosystem ecology by providing insight into the effects of large terrestrial consumers across ecosystem boundaries with potential implications for landscape‐scale management of hyper‐abundant ungulates. Given the broad availability and improvement in remote sensing technology, the novel integration of remote sensing and field studies employed here may provide a roadmap for future studies of meta‐ecosystem dynamics.